The species of Megaphragma Timberlake (Hymenoptera: Trichogrammatidae) from Argentina - Viggiani, Gennaro; Albarracin, Erica Luft; Virla, Eduardo (Zootaxa, 2009)
Trichogrammatidae are an almost worldwide family of egg parasitoids that consist of 88 genera (Pinto 2006). Species of Megaphragma Timberlake (tribe Oligositini) are egg parasitoids of Thysanoptera. Fifteen species are assigned to Megaphragma, but only three have been reported from the Neotropical region (Noyes 2002). Megaphragma mymaripenne Timberlake (1924) has been recorded previously from Argentina (De Santis 1970), but M. striatum Viggiani (1997) was known only from Mexico, and M. caribea Delvare (1993) is known only from Guadeloupe (Noyes 2002; Pinto 2006).